(untitled) (European Journal of Marketing and Economics, 2019)
The concept of trust is considered as a psychological and sociological phenomenon. Numerous theories have been developed to achieve economic development and to increase the level of welfare. The theories have not always revealed the expected results due to ignoring human behavior. Behavioral models addressing human behavior have gained importance in recent years. Thus, it was seen that emotions and thoughts were effective in creating different economic decisions. One of the factors affecting decisions is also trust. The aim of the study is to clarify the effects of the concept of trust on socio-economic life with different perspectives. When the literature is examined; There are concepts such as (i) social trust and (ii) economic trust. These concepts are related closely with some topics such as marketing and business, finance and economics. Some positive results are expected from the climate of trust. (i) With the establishment of appropriate communication between individuals, some social problems and their costs are reduced. (ii) The development of business-customer relations is beneficial for both sides. (iii) With the positive relations between fund providers and fund seekers in financial markets, financial institutions work more effectively and the markets grow. (iv) Financial growth also triggers economic growth and development. (v) Economic trust, as a measure of future assessments, increases economic activities. The study collectively evaluates the effect of the concept of trust in different areas. The findings show what kind of legal arrangements should be made by policy makers in different areas in order to increase the trust of people.